2021
DOI: 10.1093/jme/tjab099
|View full text |Cite
|
Sign up to set email alerts
|

Insect Succession and Decomposition Pattern on Pig Carrion During Warm and Cold Seasons in Kwazulu-Natal Province of South Africa

Abstract: With the aim of identifying insects with potential value as indicator species in postmortem interval (PMI), the location or season of death of human or monogastric animals, two medium-sized large white pigs were used for the study during cold and warm seasons. Five stages of decomposition and their durations were observed and described in the pig carcasses during both seasons. Carcasses were first colonized by flies from seven taxa during fresh stage. Chrysomya marginalis (Wiedemann) (Diptera: Calliphoridae), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 49 publications
(96 reference statements)
2
17
0
Order By: Relevance
“…Morphological identification based on the identification key described by ( Tourle, Downie & Villet, 2009 ; Iqbal et al, 2014 ; Lutz et al, 2018 ) classified collected dipteran flies into five genera; Chrysomya , Lucilia , Musca , Sarcophaga and one unidentified genus, and five Coleoptera families (Cleridae, Dermestidae, Silphidae, Scarabaeidae and Meloidae) ( Tembe, Malatji & Mukaratirwa, 2021 ; Tembe & Mukaratirwa, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Morphological identification based on the identification key described by ( Tourle, Downie & Villet, 2009 ; Iqbal et al, 2014 ; Lutz et al, 2018 ) classified collected dipteran flies into five genera; Chrysomya , Lucilia , Musca , Sarcophaga and one unidentified genus, and five Coleoptera families (Cleridae, Dermestidae, Silphidae, Scarabaeidae and Meloidae) ( Tembe, Malatji & Mukaratirwa, 2021 ; Tembe & Mukaratirwa, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ecosystem of the farm is typically herbaceous due to long-term burning and it falls under the Southern Tall Grassveld ( Mills & Fey, 2004 ; Kiala, Odindi & Mutanga, 2017 ). Experiments were performed during the cold season (June–August 2019) and warm season (November 2019–January 2020) with measured temperature ranging between 18–19 °C and 21–23 °C respectively ( Tembe & Mukaratirwa, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies shows a high insect community variation, mainly by habitat differences (Parry et al, 2016), food availability (T. D. C. Moretti et al, 2008), insect community structure (Tembe & Mukaratirwa, 2021), and temporal changes (Richards et al, 2009). Studies in other regions have shown that Diptera and Coleoptera account for 60% of the fauna associated with decaying carcasses, and Chrysomya sp.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other regions have shown that Diptera and Coleoptera account for 60% of the fauna associated with decaying carcasses, and Chrysomya sp. are an important gender of scavenger fauna (Haskell et al, 2008;Oliveira-Costa, 2013;Tembe & Mukaratirwa, 2021). According to Moretti et al (2008), a higher diversity of arthropods has been found in cadaveric fauna, and Chrysomya megacephala (Fabricius, 1974) may be an important specie of scavenger fauna in southern Brazil (Carvalho & Mello-Patiu, 2008;Trivia & Carvalho, 2018).…”
Section: Introductionmentioning
confidence: 99%